Main factors behind price fluctuations in food market and its impacts on purchasing power of people in Azerbaijan - Allahverdiyev, Seymur (ADA University, 2023)
Increasing food prices, high rates of inflation have significantly affected the purchasing power of consumers over the years. Price fluctuations led to the higher food insecurity, limited access to the important nutrition items and resulted in aggravation of poverty. The current scale of global crisis on hunger and undernutrition is tremendously increasing. Due to WFP (2023), it is estimated that 345 million people in 79 countries are currently facing the harsh levels of food insecurity in the year of 2023. These statistics have doubled since 2020 from the period of COVID-19. This represents a surprising increase of 200 million people in comparison to before pandemic levels. It seems that ongoing price fluctuations in the food market is going to continue as the global conflicts are aggravating and world population is increasing. Market prices for agricultural goods has significantly increased a year after Russia invaded Ukraine. Though there is a slight decrease in prices in comparison to early 2022, but still extension of the war between world’s largest exporters of wheat and other essential crops to the second year puts many countries to face the excessive food insecurity. According to IMF (2023) Fragile and conflict-affected states, home to 1 billion people, are at particular risk.
Keywords: Price fluctuations -- Azerbaijan.; Food market -- Azerbaijan.; Consumer behaviour -- Azerbaijan.; Consumer behaviour.; Public and International Affairs